Indonesia's Criminal Law Policy in Tackling Cyberbullying with a Restorative Justice Approach - Muh. Takdir; Surastini Fitriasih (LEGAL BRIEF, 2023)
The increasing number of complaints from victims of cyberbullying crimes from year to year certainly requires a criminal law policy, both through penal and non-penal efforts, which are not only repressive but also preventive. The Restorative Justice (RJ) approach is one of the possible mechanisms that can be offered in order to combat this type of crime. This study aims to explain how Indonesian criminal law regulates cyberbullying and how Restorative Justice (RJ) approach concept addresses cyberbullying. This research is normative juridical research. The legal materials used were primary legal materials taken from regulations and secondary legal materials refer to relevant writings, books or research. The data is analyzed qualitatively and the writing was organized systematically and descriptively. The results revealed that the regulation on the settlement of cyberbullying includes Article 310 paragraphs (1) and (2) of the Criminal Code, Article 311 of the Criminal Code, Article 315 of the Criminal Code, Article 27 paragraphs (3) and (4) in conjunction with Article 45 paragraph (3) and (4) Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions and Article 29 in conjunction with Article 45B of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law), in this article cannot be applied if the action is only in the form of a threat. Even so, the concept of restorative justice is regulated in law enforcement agencies as the implementation rules have not accommodated several types of cyberbullying crimes.